Aging parasites produce offspring with poor fitness prospects. (28th February 2017) - Lippens, Cédric; Faivre, Bruno; Lechenault, Clothilde; Sorci, Gabriele
Abstract : Senescing individuals have poor survival prospects and low fecundity. They can also produce offspring with reduced survival and reproductive success. We tested the effect of parental age on the performance of descendants in the nematode Heligmosomoides polygyrus, an intestinal parasite of rodents. We found that offspring of senescing worms had reduced within-host survival and reduced egg shedding over the first month post-infection compared with offspring produced by young parents. These results suggest that declining offspring quality is a component of senescence in parasitic nematodes and might have evolutionary consequences for the optimal schedule of age-dependent investment into reproductive effort.